2021
DOI: 10.3389/fpsyg.2020.618509
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience as a Protective Factor for Depression and Anxiety Among the Public During the Outbreak of COVID-19

Abstract: BackgroundPsychological resilience may reduce the impact of psychological distress to some extent. We aimed to investigate the mental health status of the public during the outbreak of coronavirus disease 2019 (COVID-19) and explore the level and related factors of anxiety and depression.MethodsFrom February 8 to March 9, 2020, 3,180 public completed the Zung’s Self-Rating Anxiety Scale (SAS) for anxiety, Zung’s Self-Rating Depression Scale (SDS) for depression, the Connor–Davidson resilience scale (CD-RISC) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 19 publications
(19 reference statements)
9
61
0
2
Order By: Relevance
“…The possible explanations for these findings could be pandemic-related increase in childcare responsibilities, lockdown measures, furlough, and loss in income, as well as possible difficulties with telemedicine access. Our findings are in line with several other studies that have reported younger patients and women were more vulnerable to the mental stress related to the pandemic ( 24 , 25 ), that easy access to telemedicine could achieve high patient’s satisfaction and meet their needs in other common endocrine conditions during the pandemic ( 26 , 27 ), and that good insurance coverage was associated with better self-perceived health in patients with AI ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…The possible explanations for these findings could be pandemic-related increase in childcare responsibilities, lockdown measures, furlough, and loss in income, as well as possible difficulties with telemedicine access. Our findings are in line with several other studies that have reported younger patients and women were more vulnerable to the mental stress related to the pandemic ( 24 , 25 ), that easy access to telemedicine could achieve high patient’s satisfaction and meet their needs in other common endocrine conditions during the pandemic ( 26 , 27 ), and that good insurance coverage was associated with better self-perceived health in patients with AI ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…A tendency score of less than zero, suggests that the subject tends to adopt a positive manner under pressure (Nie et al, 2017 ). This scale has been commonly used in Chinese, especially during the COVID-19 pandemic (Li, J. et al, 2020 ; Song et al, 2020 ; Li et al, 2021 ; Yao et al, 2021 ). In our sample, Cronbach's α was 0.90 for the SCSQ, and for two subscales, positive coping and negative coping, it was 0.89 and 0.78, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the development of the Connor–Davidson Resilience Scale (CD-RIS), the authors remarked they operationalized the construct by referring to the earlier works of the following: Kobasa on hardiness which encompassed control, commitment and viewing a change as a challenge [ 18 ]; Rutter’s work which emphasized secure relationships, self-efficacy, past success, perceived choice and action orientation as protective factors against psychiatric disorders [ 19 ]; and Lyon’s work on patience and distress tolerance for adjusting to a trauma [ 20 ]. During the COVID-19 pandemic, several studies have reported negative relationships between psychological resilience and sense of danger, and psychological distress and somatic symptoms in community samples [ 21 , 22 , 23 ]. Psychological resilience was also found to mediate the link between a pandemic-related stressful experience and acute stress disorder among a sample of Chinese university students [ 24 ].…”
Section: Introductionmentioning
confidence: 99%